Sacroiliitis after use of oral isotretinoin - association with acne fulminans or adverse effect? - Ariane Silva Bastos Geller; Roberta Ferreira Nazareth Alagia (Sociedade Brasileira de Dermatologia, 2013)
Acne fulminans is a rare and severe form of acne that may evolve from acne vulgaris, especially in male adolescents, or occur as an adverse effect of oral isotretinoin. Arthritis is a serious clinical manifestation when the musculoskeletal system is compromised by AF and has been reported as a rare adverse effect of isotretinoin. Involvement of the sacroiliac joints occurs in 21% of acne fulminans cases. We present the case of a 18-year-old male patient in whom acne fulminans evolved from acne vulgaris grade IV and after inflammation resolution started treatment with oral isotretinoin. Within a 30-day period of retinoid treatment he presented with back pain followed by rapid, progressive inability to deambulate.